Pengaruh Penggunaan T2 Blade terhadap Kualitas Citra MRI Cervical Potongan Sagital pada Pasien Non-Cooperative - Sriyatun Sriyatun; Eny Supriyaningsih; Yasinta Oktavianti (Poltekkes Kemenkes Semarang, 2023)
Background: Using T2 BLADE in Cervical MRI examination can improve image quality because it can reduce artifacts especially with Non-Cooperative patients. The purpose of this study was to analyze the effect of T2 BLADE use on sagittal cut image quality in Non-Cooperative patients. The benefit of using T2 BLADE is that it provides insight to the reader and as an alternative in selecting the right sequence on Cervical MRI examination with Non-Cooperative patients so as to get an optimal and informative picture.Methods: The research design carried out was qualitative descriptive analytic with an observation and experimental approach which was carried out from May to June 2023 at Fatmawati Hospital using a Siemens Magnetom Altea 1.5T MRI aircraft. The population of this study was samples that performed Cervical MRI examination with a total of 6 samples. The data in this study is primary data collected by observation, experiments and questionnaires. Data processing and analysis was carried out by giving questionnaires to radiologst and radiographer who made subjective assessments and processed with simple calculations using Ms. Excel to find the Mean.Results: The results of this study are, the image quality of Cervical MRI examination in Non-Cooperative patients is more optimal using T2 BLADE sequences, the resulting images have quite informative results when compared to T2 TSE sequences. This study can be an option when conducting Cervical MRI examination on Non-Cooperative patients based on questionnaires, simple calculations and author analysis, so that patients get a diagnosis accurately and quickly.Conclusions: It can be concluded that the image quality of Cervical MRI examination in Non-Cooperative patients is more optimal using T2 BLADE sequences, the resulting image has quite informative results. This study can be an option when conducting Cervical MRI examination on Non-Cooperative patients based on questionnaires, simple calculations and author analysis, so that patients get a diagnosis accurately and quickly.